2020
DOI: 10.21061/jvs.v6i2.188
|View full text |Cite
|
Sign up to set email alerts
|

Social Integration of Student Veterans: The Influence of Interactions with Faculty on Peer-Group Interactions

Abstract: Student veterans are distinct nontraditional students, inasmuch as their transition to campus is twofold. They are not only taking on the role of a student, but also their new lives as civilians. Their relationships with peers can then be strained, as the age, maturity level, and expectations may differ from the traditional-aged college student. Therefore, interactions with faculty members are imperative to help encourage student veterans' peer-group interactions. This quantitative analysis studied peer-group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…10 The way student veterans interact with their institution of higher learning can present challenges for faculty and administrators who are not familiar with the military culture. 11 College administrations can choose to support military-affiliated students in a myriad of ways, including by offering the Campus Green Zone training program, which is considered a best practice by the American Council on Education. 12 Although the Campus Green Zone concept is not standardized nationally, typically, the Campus Green Zone training workshop is geared toward faculty and frontline administrators who work directly with students in all areas of campus and academic life.…”
Section: Foundational Concepts and Contentmentioning
confidence: 99%
“…10 The way student veterans interact with their institution of higher learning can present challenges for faculty and administrators who are not familiar with the military culture. 11 College administrations can choose to support military-affiliated students in a myriad of ways, including by offering the Campus Green Zone training program, which is considered a best practice by the American Council on Education. 12 Although the Campus Green Zone concept is not standardized nationally, typically, the Campus Green Zone training workshop is geared toward faculty and frontline administrators who work directly with students in all areas of campus and academic life.…”
Section: Foundational Concepts and Contentmentioning
confidence: 99%
“…Scholars repeatedly confirm that faculty/staff are some of the most impactful agents in student veterans' transition into higher education and civilian society (Arminio et al, 2018;Dean et al, 2020), but literature suggests that many student veterans feel misunderstood and often unsupported by their professors (Griffin & Gilbert, 2015;Vacchi & Berger, 2014;Williams-Klotz & Gansemer-Topf, 2017). Several studies have reported that faculty/staff lack critical awareness about student veterans' unique cultural background leading to gaps in understanding related to cultural expectations and values (Cook & Kim, 2009;Lim et al, 2018).…”
mentioning
confidence: 99%